FORMAÇÃO DOCENTE EM NÍVEL MÉDIO NA MODALIDADE NORMAL: UM ESTUDO SOBRE AS INFLUÊNCIAS EDUCATIVAS DO CURSO NORMAL NAS TRAJETÓRIAS PROFISSIONAIS DE EGRESSOS DO COLÉGIO ESTADUAL OLAVO BILAC — CANTAGALO PR - PEREIRA, NOELI MARIA (2022)
This dissertation was prompted by the interest of analyzing to what extent the influences of the educational elements of the high school education in the normal modality, offered by the Olavo Bilac State School, located in the city of Cantagalo PR, affected the professional trajectories of four egresses who participated of the research. The unfolding of this analysis was preceded by two theoretical mediations of historical contextual nature - the focus on the emergence of the Normal School and the presentation of the historical aspects of the Olavo Bilac State College and its Normal Course, locus of the teacher training of the research subjects. For this, it was listed as a main objective, to analyze from the subjects' narratives the educational elements of high school education which influenced their professional trajectories, and as more specific intentional developments we listed, to research the historical aspects of the Normal School in Brazil and in the State of Paraná, in order to understand the identity and the specific features of this formative space, to comprehend the historical and pedagogical aspects of the Olavo Bilac State School and the Normal Course as locus of the formation of our research participants and finally to analyze in the interviews, the professional trajectories, with the purpose of intermediation with the educational influences that composed the professional path of the participating egresses. We are guided by the qualitative research approach and as instruments of data collection we used the semi-structured interview, conducted with the participants through Google Meet, whose intention was to give voice to the teachers' professional trajectories, and an on-line form, in order to draw the profile of the interviewees and better qualify them, the analysis of qualitative data was performed from the Content Analysis technique provided by Bardin (2011). From the interviews, it was possible to formulate three main categories for investigation, 1) initial training, 2) teaching knowledge and 3) teaching trajectories, with these, it was possible to face the main topic. The research allowed us to observe that, historically, teacher training policies have been influenced by the hegemonic class of their own time and context, which meant models transplanted from abroad, dictates from international organizations, intermittent periods of the existence of formation institutions at the high school level, and even disruption of public policies for teacher training in this area of education. The hypotheses of the investigation with the research subjects highlighted a direct and correlated relationship of the training obtained in the normal high school with the progress on the teaching career, revealing that the training in high school contributed to the professional trajectories, whether in the field of teaching, management, or research, in their teaching knowledge and in their choices related to the continuity of the teaching professionalization until the present moment.